The effect of caregiver opinion leaders to increase demand for evidence-based practices for youth anxiety: A cluster randomized controlled trial - Margaret E. Crane; Marc S. Atkins; Sara J. Becker; Jonathan Purtle; Gillian C. Dysart; Sydney Keller; Olivia Brauer; Sirina E. Tiwari; Thomas M. Olino; Lara Baez; John Lestino; Philip C. Kendall (Implementation Research and Practice)
Background Dissemination initiatives have the potential to increase consumer knowledge of and engagement with evidence-based treatments (e.g., cognitive behavioral therapy [CBT]). Opinion leaders (OLs) have been used in public health campaigns, but have not been examined for the dissemination of mental health treatments. This study uses the Theory of Planned Behavior to test the dissemination strategy of involving an OL in an educational presentation to increase caregiver demand for CBT for youth anxiety. Method Participants ( N  = 262; 92% female; 69% White, 82% non-Hispanic) were caregivers who registered for a virtual presentation on youth anxiety treatment through their child's school. Schools within 1.5-hr drive of Philadelphia, PA were cluster-randomized ( k  = 25; two-arm prospective randomization) to the OL condition (presented by a clinical researcher and local caregiver OL; n  = 119 participants) or the researcher-only condition ( n  = 143 participants). Presentations occurred from May 2021 to May 2022. Measures were completed pre- and post-presentation and at 3-month follow-up. Results Relative to the researcher co-presenter, participants rated the OL as significantly more relatable, familiar, similar, and understanding of their community, but less credible than the researcher co-presenter. In both conditions, there was a significant pre-post increase in participants’ knowledge of, attitudes about, subjective norms related to, and intention of seeking CBT for youth anxiety, but not stigma. Presentation conditions did not differ in change on these measures, or on rates of seeking youth anxiety CBT at follow-up. Conclusions Although involvement of a caregiver OL did not increase caregiver demand for evidence-based treatment for youth anxiety, the outreach presentation was associated with increases in knowledge of, attitudes about, subjective norms related to, and intention to seek CBT for youth anxiety. Involving OLs in researcher-delivered dissemination efforts may not be necessary for all consumer audiences, but may be beneficial for engendering a sense of relatability, similarity, and connection with disseminators.